Updating the distribution of sand flies in Hungary with implications on their biology and ecology - Platzgummer, Katharina; Kniha, Edwin; Dvorak, Vít; Halada, Petr; Walochnik, Julia; Vomackova Kykalova, Barbora; Hanusniakova, Ida; Farkas, Robert; Volf, Petr; Trájer, Attila J (Current research in parasitology & vector-borne diseases, 2025)
In Europe, sand flies (Diptera: Psychodidae: Phlebotominae) are characteristic Mediterranean fauna, though some species expand their range further north. However, the sand fly fauna of Central Europe remains underreported, particularly in Hungary where recent data is lacking due to limited and outdated entomological surveys. To address this gap, a series of sand fly surveys were conducted in Hungary, with significant findings from two trapping efforts in 2017 and 2024. In 2017, only a single female Phlebotomus papatasi was trapped in northern Hungary, which marks one of the northernmost records of the species. In 2024, a more extensive and geographically wider survey recorded 264 sand flies at 34 sites, including three species: Ph. mascittii, Ph. neglectus, and Ph. papatasi. Sand flies were found across diverse environmental settings, including urban, agricultural, and natural habitats. Particularly, the previously rare presence of Ph. mascittii at rural sites (natural rock formations) was reported. Analysis of historical and current data revealed the presence of four sand fly species in Central and South Transdanubia, with evidence suggesting potential range expansion. Blood meal analysis of engorged females identified a variety of domestic and wild host species, but no Leishmania or Phlebovirus infections were detected. Habitat modelling and linear discriminant analysis indicated substantial climate suitability across Southeast Europe, with most positive sand fly observations observed in discontinuous urban fabric CORINE Land Cover classes. This study offers important insights into the ecology, distribution, and climatic preferences of sand flies in Hungary and provides crucial baseline data to monitor potential future spread.
Keywords: MALDI-MS; Barcoding; Ecology; Blood meal; Central Europe; Sand flies